2018
DOI: 10.1186/s13063-018-2802-5
|View full text |Cite
|
Sign up to set email alerts
|

Yoga and breathing technique training in patients with heart failure and preserved ejection fraction: study protocol for a randomized clinical trial

Abstract: BackgroundCurrent therapies for heart failure (HF) are followed by strategies to improve quality of life and exercise tolerance, besides reducing morbidity and mortality. Some HF patients present changes in the musculoskeletal system and inspiratory muscle weakness, which may be restored by inspiratory muscle training, thus increasing respiratory muscle strength and endurance, maximal oxygen uptake (VO2), functional capacity, respiratory responses to exercise, and quality of life. Yoga therapies have been show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 29 publications
1
22
0
1
Order By: Relevance
“…[ 21 ] Regular exercise, yoga asanas, pranayama, and meditation have been shown to prevent and correct these abnormalities[ 22 23 ] Studies point to the beneficial effect of yoga in maintaining physiological balance of lipid profile parameters[ 6 24 3 ] and prevention of the related cardiac complications. [ 26 ] Other studies[ 27 ] also point to the beneficial effects of physical exercises in ameliorating dyslipidemia by upregulating HDL levels and downregulating LDL and TGL;[ 28 ] it has been reported that HDL seems to play a key role in maintaining triglyceride levels. [ 29 ] Further, Kumari et al ., 2013,[ 30 ] looking at the mechanism points out that Yoga practices may improve the lipid profile in by elevating hepatic lipase activity which may facilitate better triglyceride metabolism in the adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] Regular exercise, yoga asanas, pranayama, and meditation have been shown to prevent and correct these abnormalities[ 22 23 ] Studies point to the beneficial effect of yoga in maintaining physiological balance of lipid profile parameters[ 6 24 3 ] and prevention of the related cardiac complications. [ 26 ] Other studies[ 27 ] also point to the beneficial effects of physical exercises in ameliorating dyslipidemia by upregulating HDL levels and downregulating LDL and TGL;[ 28 ] it has been reported that HDL seems to play a key role in maintaining triglyceride levels. [ 29 ] Further, Kumari et al ., 2013,[ 30 ] looking at the mechanism points out that Yoga practices may improve the lipid profile in by elevating hepatic lipase activity which may facilitate better triglyceride metabolism in the adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…It showed no change in the pooled results after excluded individual studies. An RCT on the role of yoga and breathing exercise in HFpEF is currently ongoing so we couldn’t analyze its data but once it will be complete, it will certainly be helpful to explore more on the topic of breathing [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we have shifted our gaze to evaluate inspiratory muscle training for improving quality of life and cardiorespiratory fitness in patients with stable HFpEF. We have used peak oxygen consumption (Peak VO 2 ) and six-min walk distance (6MWD) as a marker of cardiorespiratory fitness and quality of life in HFpEF patients [4,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Ayurveda boosts comprehensive wellbeing, which include eating routine, rest, mental unwinding, way of life conduct, and Yoga Pranayama (Breathing techniques) is known to enhance lung capacity. (Lopes et al, 2018) Yoga and meditation are simple and affective for various other illnesses also. (Tillu et al, 2020a).…”
Section: Ashwagandhamentioning
confidence: 99%